A mild one-pot synthesis of 2-iminothiazolines from thioureas and 1-bromo-1-nitroalkenes. Issue 4 (8th January 2021) - Xu, Yuan; Ge, Xin; Zhang, Yuhan; Zhang, Hongbin; Liu, Xue-Wei
Abstract : A mild method to access functionalized 2-iminothiazolines in a facile and efficient manner has been developed. Abstract : A mild method to access functionalized 2-iminothiazolines in a facile and efficient manner has been developed. The reaction started from 1, 3-disubstituted thioureas and 1-bromo-1-nitroalkenes in the presence of triethylamine in THF and proceeded smoothly in air to afford 2-iminothiazoline derivatives in moderate to good yields.